DISCOUNT PRICING. (5th March 2019) - Armstrong, Mark; Chen, Yongmin
Abstract : We investigate the practice of framing a price as a discount from an earlier price, with information such as "was 200, now 100." We discuss two reasons why a discounted price—rather than a merely low price—can make a consumer more willing to purchase. First, a high initial price can indicate the seller has chosen to supply a high‐quality product. Second, when a seller with limited stock runs a clearance sale, later consumers infer that unsold stock has higher expected quality when its initial price was higher. We also suggest a behavioral explanation, which is that consumers with reference‐dependence preferences are more likely to buy if they perceive the price as a bargain relative to the earlier price. Discount pricing is therefore an effective marketing technique, and a seller may wish to deceive potential customers by offering a false discount. The welfare effects of regulation to prevent fictitious pricing are subtle, with potential unintended consequences, and depend on whether consumers are sophisticated or naive. ( JEL D18, D42, D83, L15, M31)